Synthesis and Spectral studies of some (IIb) ions with 2 – [ ( 6 – Nitro – 2 – Benzothiazolyl ) azo – 4 , 5 – diphenyl imidazole and Their Biological Activity - Hussein, Ashwaq Saleh (Al-Qadisiyah Journal of Pure Science, 2018)
This study is concerned with imidazole azo reagent ( 6 – NO2 BTADI ) 2 – ( 6 – nitro – 2 – benzothiazolyl ) azo ] – 4 , 5 – diphenylimidazole and its complexation with (Zinc( Zn+2) , Mercury(Hg+2) ) ions . The optimum conditions of these complexes were studied , such as pH values , The effect of time and temperature on a formation of the complexes .Beers law is obeyed in the concentration rang of (1-10)ug.ml -1. The expected structures of these complexes were obtained by mole ratio method , the result showed that all of these complexes have amole ratio ( 1 : 2 ) ( metal : reagent ) . Stability constants calculations and melting points measurements , conductivity , IR , UV – Vis spectra and antibacterial activity of the complexes were done.